Comprehensive Analysis to Identify MAGEA3 Expression Correlated With Immune Infiltrates and Lymph Node Metastasis in Gastric Cancer - Jin, Jinji; Tu, Jianxin; Ren, Jiahuan; Cai, Yiqi; Chen, Wenjing; Zhang, Lifang; Zhang, Qiyu; Zhu, Guanbao (Frontiers in Oncology, 2021)
Gastric Cancer is an aggressive disease and remains one of the leading causes of cancer-related death worldwide. With the coming of the age of cancer immunotherapy, search for a new target in gastric cancer may benefit more advanced patients. Melanoma-associated antigen-A3 (MAGE-A3) is a tumor-specific antigen and the MAGE-A3 immunotherapeutic was part of a research program developing antigen-specific cancer immunotherapeutics. We assess the role of MAGEA3 in GC, via the publicly available TCGA and GEO database. The result revealed that MAGEA3 is upregulated in GC, and high MAGEA3 expression was linked to the poor OS and lymph node metastasis of gastric cancer. MAGEA3 was also correlated with immune checkpoints, TMB, and have an impact on the changes in the tumor immune microenvironment and the prognosis of GC through CIBERSORT, TIMER and Kaplan-Meier plotter database analysis. In addition, GSEA identified MAGEA3 is involved in the immune regulation of GC. Moreover, the protein-protein interaction (PPI) networks of MAGEA3 were developed utilizing the STRING database and MAGEA3 correlated miRNAs were screened based on the joint analysis of multiple databases. In terms of experimental verification, we constructed pET21a (+)/MAGE-A3 restructuring plasmids, and transformed to E.coil Rosetta. Using purified MAGE-A3 as an antigen, the presence of specific IgG in the serum specimens of 93 gastric cancer patients was effectively detected with 44.08% sensitivity and 92.54% specificity. Through further analysis, the positive rate of MAGE-A3 may be related to the stage of gastric cancer and transfer number of lymph nodes. Those results indicated that MAGEA3 is a novel biomarker and correlated with lymph node metastasis and Immune Infiltrates in GC, which can be a potential target antigen for Gastric cancer immunotherapy.